Report of silverstripe blassop, Lagocephalus sceleratus (Gmelin, 1789) (Tetraodontidae) from south-west coast of India - Bineesh, K. K.; Joshi, K. K.; Abdussamad, E. M.; Prakashan, D.; Akhilesh, K. V. (Indian Journal of Fisheries, 2014)
The silverstripe blassop, Lagocephalus sceleratus (Gmelin, 1789), is reported from the south-west coast of India (Kerala coast), which is characterised by a grey-brownish dorsal surface with black, regularly distributed spots of equal size and a wide silver band laterally on each side. The specimen collected is described and figured.